Research on the Balance between Consumer Protection Law and Market Freedom in the Era of E-Commerce - Feng, Lisha (International Journal of Social Sciences and Public Administration, 2025)
With the rapid development of e-commerce, consumers are facing many risks and challenges while enjoying convenient transactions. This paper first reviews the related concepts of e-commerce and market freedom, and analyzes the mutual influence and conflict between them in practical application. Secondly, it discusses how to balance consumer protection and market freedom through legal means in specific issues such as telecommunications tariffs and certification of violations. Finally, this paper puts forward some policy suggestions, such as improving the system construction, improving the social environment and strengthening the data protection, in order to promote the perfection of the legal system and the stability of the market order in the era of e-commerce.